HUBUNGAN ANTARA KEKUATAN OTOT TUNGKAI DENGAN HASIL BELAJAR LOMPAT JANGKIT SISWA SMAN 1 TAMAN - RUDHIE PRASETYA, RIAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education is one of the subject study that giving by the teacher from education in the elementary school until senior high school. Pass through the physical education student get socialization physical activity that conclude on skill physical exercise one of them is teaching triple jump. Because like that, need more a wise knowledge, so we can know about all of the factor that give an influence to the result study of student in doing jump, so the teacher don’t have any difficulties in the implementation to reached the great achievement of the student. This research have a purpose to know about the relationship between the strength of leg muscle with the study result of triple jump student of SMAN 1 Taman, and to know bigness contribution of leg muscle with the study result of triple jump student of SMAN 1 Taman. The kind of research that the researcher use is quantitative approach research, Population in observational it’s student class XII SMAN 1 Taman, outgrow population 310 person, for the sample of researcher using random sampling technique. In getting the data, researcher doing the test with using Leg Dynamometer as tools to know the strength of leg muscle after that, is a test for a skilled triple jump. According to the result of manual counting found that the relationship between the strength of leg muscle with the result study of triple jump student of SMAN 1 Taman is rcount (0,820) > rtable (0,355) with using standard significant 5%. While the coefficient determination 67,24 this case have a meaning that the contribution of statistical variable of the strength of leg muscle with the result study of triple jump student of SMAN 1 Taman  is 67,24% while the residue is 32,76% get influence from another statistical variable. From the counting data analyze get conclude that there is a relationship between the strength significant of leg muscle with the result study of triple jump students of SMAN 1 Taman. So the teacher can more easy in the giving treatment to reached a maximal achievement of the student. Keywords : The strength of leg muscle, the result study of triple jump.